Apocrine-eccrine carcinomas: molecular and immunohistochemical analyses. - Long P Le (PLoS ONE, 2012)
Apocrine-eccrine carcinomas are rare and associated with poor prognosis. Currently there is no uniform treatment guideline. Chemotherapeutic drugs that selectively target cancer-promoting pathways may complement conventional therapeutic approaches. However, studies on genetic alterations and EGFR and Her2 status of apocrine-eccrine carcinomas are few in number. In addition, hormonal studies have not been comprehensive and performed only on certain subsets of apocrine-eccrine carcinomas. To investigate whether apocrine-eccrine carcinomas express hormonal receptors or possess activation of oncogenic pathways that can be targeted by available chemotherapeutic agent we performed immunohistochemistry for AR, PR, ER, EGFR, and HER2 expression; fluorescence in situ hybridization (FISH) for EGFR and ERBB2 gene amplification; and molecular analyses for recurrent mutations in 15 cancer genes including AKT-1, EGFR, PIK3CA, and TP53 on 54 cases of apocrine-eccrine carcinomas. They include 10 apocrine carcinomas, 7 eccrine carcinomas, 9 aggressive digital papillary adenocarcinomas, 10 hidradenocarcinomas, 11 porocarcinomas, 1 adenoid cystic carcinoma, 4 malignant chondroid syringomas, 1 malignant spiradenoma, and 1 malignant cylindroma. AR, ER, PR, EGFR and HER2 expression was seen in 36% (19/53), 27% (14/51), 16% (8/51), 85% (44/52) and 12% (6/52), respectively. Polysomy or trisomy of EGFR was detected by FISH in 30% (14/46). Mutations of AKT-1, PIK3CA, and TP53 were detected in 1, 3, and 7 cases, respectively (11/47, 23%). Additional investigation regarding the potential treatment of rare cases of apocrine-eccrine carcinomas with PI3K/Akt/mTOR pathway inhibitors, currently in clinical testing, may be of clinical interest.